A translational evaluation of listener interest on the presentation of conversation topics to individuals who exhibit restricted interests. Issue 3 (23rd March 2022) - Fakharzadeh, Sadaf; Stocco, Corey S.
Abstract : Listener behavior has been shown to influence speaker behavior. However, little is known about the extent to which listener behavior can influence countertherapeutic outcomes. This study evaluated the influence of listener interest on the topics presented by adult participants conversing with an experimenter acting as an individual who exhibited restricted interests. Each session consisted of a 5‐min conversation, during which the participant was instructed to talk about 3 topics. We compared the duration of topic presentation across phases in which the experimenter behaved as an interested listener for 1 topic or for all 3 topics. Results showed that topic presentation was controlled by listener interest and all participants reported that the simulation was believable, acceptable, and useful. Although preliminary, these findings have implications for understanding possible undesirable interactions between individuals diagnosed with autism spectrum disorder who exhibit restricted interests and their peers or caregivers.